Haemin enhancement of glucose transport in human lymphocytes: stimulation of protein tyrosine phosphatase and activation of p56lck tyrosine kinase. - Lander, H M (1993)
Following our previous observation that haemin is mitogenic for human lymphocytes, we investigated the ability of haemin to enhance glucose uptake in these cells. We found that preincubation of human peripheral-blood mononuclear cells (PBMC) with haemin for 60 min increased up to 5-fold the rate of 2-deoxy-D-[1-3H]glucose uptake by the cells. Actinomycin D and cycloheximide did not inhibit the effect, and cytochalasin B completely blocked it. Among the metalloporphyrins tested (Fe-, Ni-, Co-, Zn- and Sn-protoporphyrin), only haemin (Fe-protoporphyrin) induced a marked increase in glucose uptake. Thiourea, a scavenger of oxygen free radicals, and 3-amino-1,2,4-triazole inhibited haemin-induced glucose uptake. Oxidants such as H2O2 and phenylarsine oxide were previously reported to stimulate protein tyrosine phosphorylation and to enhance glucose uptake. We found that incubation of PBMC with haemin resulted in an increase in protein tyrosine phosphatase (PTPase) activity, probably that identified as CD45. Similarly to haemin, we found that phytohaemagglutinin also enhanced PTPase activity. Haemin also activated the tyrosine kinase p56lck, which is negatively controlled by phosphorylation of Tyr-505 at the C-terminus, and increased protein tyrosine phosphorylation in these cells. Tyrphostins, specific inhibitors of tyrosine kinases, at low concentrations markedly enhanced glucose uptake and synergized with haemin in enhancing glucose uptake. At high doses, tyrphostins inhibited the effect of haemin. Taken together, we postulate that haemin enhancement of glucose uptake in human lymphocytes results from its stimulation of PTPase, followed by activation of tyrosine kinase p56lck, leading to an increase in protein tyrosine phosphorylation.